Green Visual Communication: Model Konseptual Desain Komunikasi Visual untuk Mendukung Perilaku Konsumsi Berkelanjutan - Dindatul Afizah; Ary Ramadhan (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
Transforming consumer behavior has become a fundamental requirement for achieving the Sustainable Development Goals (SDGs), particularly SDG 12 on responsible consumption and production. Although research on sustainable consumption behavior has expanded considerably, existing studies are largely dominated by green marketing and consumer psychology perspectives, while the role of visual communication design as a behavioral change mechanism remains underexplored. This study aims to develop a conceptual model of  Green Visual Communication (GVC) that explains how visual communication design can promote sustainable consumption behavior. The study adopts a conceptual paper approach by conducting a critical synthesis of theories and previous studies in visual communication design, persuasive communication, Environmental Psychology, and sustainable consumption behavior. The proposed framework integrates Visual Communication Theory, the Elaboration Likelihood Model (ELM), the Theory of Planned Behavior (TPB), and Environmental Psychology to explain the psychological processes underlying behavioral change. The findings suggest that  Green Visual Communication comprises six key dimensions: visual hierarchy, ecological color, typography readability, eco-label clarity, visual storytelling, and digital interactivity. These dimensions influence visual attention, cognitive elaboration, emotional engagement, environmental attitudes, and green purchase intention before ultimately leading to sustainable consumption behavior. The proposed model contributes theoretically by introducing  Green Visual Communication as a novel conceptual framework that integrates visual communication design with sustainability-oriented behavioral change. Practically, the framework provides strategic guidance for designers, businesses, and policymakers in developing more effective visual communication strategies to encourage responsible consumption and support the achievement of SDG 12.